The Effect of Product Quality on Customer Satisfaction Ms Glow Consumers (Study on MS Glow in North Jakarta) - Muhammad Qiamuddin; Budi Santosa Kramadibrata (Ethics and Law Journal: Business and Notary, 2023)
At this time the company is required to apply the quality standards of the products and services it produces. This study aims to determine the effect of product quality  on consumer satisfaction as one of the most popular beauty products. This study was conducted with a quantitative approach and associative research design with a sample of 127 respondents. The instrument used by researchers is a questionnaire. Quality testing on research instruments is a test of validity and reliability. Data analysis uses descriptive analysis, while for hypothesis testing using multiple linear regression analysis with the help of Statistical Package for Social Sciences (SPSS) 25. The results of this study explain that there is relationship between product quality on consumer satisfaction with a correlation coefficient value below 0.05. This analysis is only carried out in one company and does not consider other variables or moderator variables that influence customer satisfaction.